Modified human factor analysis and classification system for passenger vessel accidents (HFACS-PV). (1st August 2018) - Uğurlu, Özkan; Yıldız, Serdar; Loughney, Sean; Wang, Jin
Abstract: With the increase in the carrying capacity of passenger vessels parallel to technological developments over the last 25 years, accidents resulting in loss of lives have increased. Thus, accidents involving passenger vessels have become a major issue of concern in the maritime industry. In this study, 70 ship collision & contact accidents involving passenger vessels between 1991 and 2015 were examined. Unlike other studies in the literature, this investigation proposes a customized Human Factors Analysis and Classification System for Passenger Vessel Accidents (HFACS-PV) to facilitate analysing the human factor in passenger vessel accidents. In addition to the core HFACS structure, an additional operational condition level has been defined. The violations framework has been divided into the three sub-categories of rule violations, procedure violations, and abuse of authority, instead of the two broad categories of routine and exceptional violations. Abuse of authority is an intentional violation made knowingly and wilfully, therefore, abuse of authority has been considered separately. Furthermore, appropriate modifications have been made to the headings under the second level of HFACS-Preconditions for Unsafe Acts for compliance with the maritime industry. Highlights: Subcategories of HFACS's main levels were adapted to the maritime industry and passenger vessels. Modified HFACS-PV structure analyses accidents in 5 levels. Proposed a modified HFACS structure for analysing passenger vessel accidents, based on core HFACS structure.